Development of an Android-Based Interactive Learning Application (PIBA APDRA) on Drama Appreciation Material for Students of the Indonesian Language Education Study Program - Moh Shofiuddin Shofi; Ghulam Arif Rizal (Jurnal Ilmiah Mandala Education (JIME), 2025)
The purpose of this study is to determine the feasibility of Android-based learning media for drama appreciation materials for students of the Indonesian Language Education Study Program. The development method used is the ADDIE model. However, this research was limited to the Development stage. Based on the assessment results from three validators, the average score obtained was 74%. This indicates that the Android-based learning media for drama appreciation is categorized as feasible for use. The results were obtained from three validators: the material validator (70%), the media validator (75%), and the language validator (79%).